2003
DOI: 10.1016/s0002-9440(10)63658-9
|View full text |Cite
|
Sign up to set email alerts
|

Fibroblasts Isolated from Normal Lungs and Those with Idiopathic Pulmonary Fibrosis Differ in Interleukin-6/gp130-Mediated Cell Signaling and Proliferation

Abstract: Interleukin (IL)-6 and IL-11 are elevated in a variety of lung conditions and may impact on repair mechanisms in chronic inflammatory disorders. However, the mechanisms by which these cytokines influence fibroblast proliferation in normal and disease states have not been previously addressed. We examined the effect of these cytokines on proliferation and cell-cycle kinetics of primary human lung fibroblasts obtained from normal patients and patients with idiopathic pulmonary fibrosis (IPF). IL-6 inhibited the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
115
0
1

Year Published

2005
2005
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 146 publications
(122 citation statements)
references
References 34 publications
6
115
0
1
Order By: Relevance
“…There is evidence of aberrant alveolar epithelial repair, with increased metaplastic alveolar epithelial cells that apparently do not properly differentiate to a type I phenotype (29). Inflammatory cells are recruited to sites of epithelial injury, with subsequent release of cytokines and growth factors that promote matrix deposition and fibroblast, as well as epithelial proliferation (30). The increased fibroblasts in the lung, whether recruited from outside the lung (31) or generated via EMT (32), subsequently proliferate and deposit extensive extracellular matrix (e.g., fibronectin, collagen type I and III).…”
Section: Discussionmentioning
confidence: 99%
“…There is evidence of aberrant alveolar epithelial repair, with increased metaplastic alveolar epithelial cells that apparently do not properly differentiate to a type I phenotype (29). Inflammatory cells are recruited to sites of epithelial injury, with subsequent release of cytokines and growth factors that promote matrix deposition and fibroblast, as well as epithelial proliferation (30). The increased fibroblasts in the lung, whether recruited from outside the lung (31) or generated via EMT (32), subsequently proliferate and deposit extensive extracellular matrix (e.g., fibronectin, collagen type I and III).…”
Section: Discussionmentioning
confidence: 99%
“…4,28 In addition, fibroblasts from IPF patients have been reported to be more resistant to apoptosis than those from patients without pulmonary fibrosis. 5,6,33 Moodley and co-workers 5 have suggested that the altered IL-6 signaling in fibroblasts from IPF patients may enhance the resistance of these cells to apoptosis and thus contribute to pulmonary fibrosis. Tanaka and co-workers 6 showed that resistance to FasLinduced apoptosis in human primary lung fibroblasts is associated with the expression of anti-apoptotic proteins such as X chromosome-linked inhibitor of apoptosis and FLICE-like inhibitor protein, which are up-regulated in the lungs of IPF patients.…”
Section: Discussionmentioning
confidence: 99%
“…Protein extracts (in 1% sodium dodecyl sulfate; 30 g of total protein/lane) were analyzed by sodium dodecyl sulfate-polyacrylamide gel electrophoresis on 12.5% acrylamide gels, as previously described. 23,24 Western blot analysis was performed with antibodies to phospho-Smad2 and Smad2 (Cell Signaling Technology, Danvers, MA), matrix metalloproteinase (MMP)-13 (Calbiochem, San Diego, CA), and a goat antirabbit secondary antibody (1:1000 dilution; Bio-Rad). Blots were probed with the ECL detection kit (Amersham Pharmacia Biotech Ltd, Buckinghamshire, UK), according to the manufacturer's instructions, before being quantified by densitometry, using a Bio-Rad GS710 calibrated imaging densitometer and Quantity-One software (BioRad).…”
Section: Western Blot Analysismentioning
confidence: 99%